ENGLISH TEACHERS’ STRATEGIES IN ASSESSING EIGHTH GRADERS' SPEAKING SKILL - Ayu Yulia Fitri; Gita Mutiara Hati; Azhar Aziz Lubis (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2021)
The objective of the research are to find the strategies used by teachers in assessing speaking at SMPN 9 Kota Bengkulu. This research was quantitative approach. The subjects were twelve English lesson plans who use at eighth grade. The data were collected from documentation. The results showed that lesson plans were used five strategies from fourteen strategies in assessing speaking namely Oral Presentation, News Event, Roleplay, Discussion & Conversation, and Giving Instruction/Direction. In addition, online lesson plans used two strategies from fourteen strategies and offline lesson plans used four strategies from fourteen strategies. Further, the other nine strategies are not appeared in the class such as Repetition, Directed Response, Read Aloud, Sentence/Dialogue Completion, Question and Answer, Paraphrasing, Interview, Games and Story Telling. It can be happened because the lesson plans applied the strategies based on the students’ material, need, and condition in the meeting.